Analysis of Underdeveloped Regency Using Logistic Threshold Regression Model - Salsabila, Annisa Nur; Oktora, Siskarossa Ika (Jurnal Varian, 2024)
Regional development inequality causes some regions to lag behind other regions. An underdevelopedregency is a regency where territories and people are less developed than other regions nationally. Thegovernment has set a Human Development Index (HDI) target of 62.2 to 62.7 to accelerate the development of underdeveloped regency and prevent the regions from lagging. This study aims to evaluatethe HDI target and obtain the HDI value that reduces the risk of underdeveloped regency and acquiresvariables that affect underdeveloped regency’s status. The logistic threshold regression model is usedin this study with HDI as the threshold variable, 22 indicators for determining underdeveloped regencyas explanatory variables, and the underdeveloped regency’s status as the response variable. Thresholdregression can handle non-linear relationships between response and explanatory variables, includingvarious types of threshold models such as step, segmented, hinge, stegmented, and upper hinge. By applying a hinge threshold regression model using the R package ’chngpt,’ this study addresses non-linearrelationships and categorical responses. The results showed a threshold effect with a threshold value of62.9, indicating that the HDI target can reduce the region’s risk of being left behind.